Endothelial NADPH oxidase 4 protects ApoE-/- mice from atherosclerotic lesions - Craige, Siobhan M.; Kant, Shashi; Reif, Michaella; Chen, Kai; Pei, Yongmei; Angoff, Rebecca; Sugamura, Koichi; Fitzgibbons, Timothy; Keaney, John F. (Free radical biology & medicine, 2015)
Vascular reactive oxygen species (ROS) are known to be involved in atherosclerosis development and progression. NADPH oxidase 4 (Nox4) is a constitutively active ROS-producing enzyme that is highly expressed in the vascular endothelium. Nox4 is unique in its biology and has been implicated in vascular repair, however, the role of Nox4 in atherosclerosis is unknown. Therefore, to determine the effect of endothelial Nox4 on development of atherosclerosis, Apoe E-/- mice +/- endothelial Nox4 (ApoE-/- + EC Nox4) were fed a high cholesterol/high fat (Western) diet for 24 weeks. Significantly fewer atherosclerotic lesions were observed in the ApoE-/- + EC Nox4 mice as compared to the ApoE-/- littermates, which was most striking in the abdominal region of the aorta. In addition, markers of T cell populations were markedly different between the groups; T regulatory cell marker (FoxP3) was increased whereas T effector cell marker (T-bet) was decreased in aorta from ApoE-/- + EC Nox4 mice compared to ApoE-/- alone. We also observed decreased monokine induced by gamma interferon (MIG; CXCL9), a cytokine known to recruit and activate T cells, in plasma and tissue from ApoE-/- + EC Nox4 mice. To further investigate the link between endothelial Nox4 and MIG expression, we utilized cultured endothelial cells from our EC Nox4 transgenic mice and human cells with adenoviral overexpression of Nox4. In these cultured cells, upregulation of Nox4 attenuated endothelial cell MIG expression in response to interferon-gamma. Together these data suggest that endothelial Nox4 expression reduces MIG production and promotes a T cell distribution that favors repair over inflammation, leading to protection from atherosclerosis. [Display omitted] •NADPH oxidase 4 (Nox4) in the endothelium protects ApoE-/- mice from atherosclerosis.•Plasma monokine of interferon gamma was decreased with endothelial Nox4 expression.•Aorta from Nox4 mice had increased T regulatory and decreased T effector cell markers.•Endothelial Nox4 promotes repair by altering the localized T cell populations.